The Signature of Maternal Social Rank in Placenta Deoxyribonucleic Acid Methylation Profiles in Rhesus Monkeys. Issue 3 (14th October 2016) - Massart, Renaud; Suderman, Matthew J.; Nemoda, Zsofia; Sutti, Sheila; Ruggiero, Angela M.; Dettmer, Amanda M.; Suomi, Stephen J.; Szyf, Moshe
Abstract : The effects of social status on human health can be modeled in captive cohorts of nonhuman primates. This study shows that maternal social rank is associated with broad changes in DNA methylation in placentae of rhesus monkeys ( N  = 10). Differentially methylated genes between social ranks are enriched in signaling pathways playing major roles in placenta physiology. Moreover, the authors found significant overlaps with genes whose expression was previously associated with social rank in adult rhesus monkeys (Tung et al., 2012) and whose methylation was associated with perinatal stress in newborn humans and rhesus monkeys (Nieratschker et al., 2014). These results are consistent with the hypothesis that system‐wide epigenetic changes in multiple tissues are involved in long‐term adaptations to the social environment.